2016
DOI: 10.1177/0021998316679017
|View full text |Cite
|
Sign up to set email alerts
|

Fractography analysis of 1.0 wt% nanoclay/multi-layer graphene reinforced epoxy nanocomposites

Abstract: Abstract:The topographical features of fractured tensile, flexural, K1C, and impact specimens of 1.0 wt% Multi-Layer Graphene (MLG)/nanoclay-epoxy (EP) nanocomposites have been investigated. The topographical features studied include maximum roughness height (Rmax or Rz), root mean square value (Rq), roughness average (Ra), and waviness (Wa). Due to deflection and bifurcation of the cracks by nanofillers, specific fracture patterns are observed. Although these fracture patterns seem aesthetically appealing, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The KIC values are a function of nano clay loading and are modestly higher than that of the neat epoxy (Figure 3). This agrees well with the results reported in the literature [7,24,26,27,[29][30][31][32][33]. The fracture toughness of the neat epoxy is 0.8MPam0.5.…”
Section: Resultssupporting
confidence: 92%
“…The KIC values are a function of nano clay loading and are modestly higher than that of the neat epoxy (Figure 3). This agrees well with the results reported in the literature [7,24,26,27,[29][30][31][32][33]. The fracture toughness of the neat epoxy is 0.8MPam0.5.…”
Section: Resultssupporting
confidence: 92%
“…They also have been used as nanoreactors and adsorbents [23]. The mechanical properties of systems with halloysite nanoclay are not the only improvements that can be observed [24][25][26]. The incorporation of halloysite nanoclay enhanced the nanocomposites' thermal stability and flame and corrosion resistance of composites as well [27].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, samples reinforced with halloysite nanoclay showed less softening effect caused by methanol exposure. For higher microhardness values, the indenter hits perfectly on halloysite nanoclay tubes and the nano-filler can provide excellent resistant toward indentation because of its high surface ratio [35]. Previous research also revealed that methanol could have the highest diffusion rate and greatest degree of swelling on monolithic polyester [48].…”
Section: Resultsmentioning
confidence: 99%
“…After the images were captured and saved in the computer, the crack length that retains a spot of light focused at the sample surface [35]. An electric motor controls the upright movement and interacts to the sample surface [36] [37].…”
Section: -56-1:)mentioning
confidence: 99%